Histochemical and Immunohistochemical Study of Peripolar Cells in Sheep. (29th April 2013) - Joana, Passos; Justina, Prada; Lígia, Bento; Paula, Rodrigues; Isabel, Pires
Abstract : Peripolar cells are granulated cells located in the vascular pole of the renal corpuscle. Even though these cells have already been described, there are still many unknown histological and physiological characteristics. We carried out histochemical and immunohistochemical analyses of peripolar cells in sheep and compared their number in both normal and injured kidneys, discriminating according to the age of the animal. We tested HE, Toluidine Blue, PAS, and Masson's Trichrome stains to select the best stain for identification and quantification. Masson Trichrome yielded the best results and was selected for this purpose. We identified the cells by the presence of cytoplasmatic granules and by their position in the vascular pole. We found no statistically significant association between the number of peripolar cells and the age of the animal or the occurrence of lesions. In the immunohistochemical analysis, we found that the cells were positive to α -smooth muscle actin and less consistently positive to NSE and S100 protein. Chromogranin A, cyclooxygenase-2, AE1/AE3, and Wide Spectrum Cytokeratin and desmin yielded negative results. We conclude that although there was evidence of a contractile function, there was no evidence to support that peripolar cells have either a neuroendocrine or an epithelial nature.